Efficacy and safety of ultra‐rapid lispro versus lispro in children and adolescents with type 1 diabetes: The PRONTO‐Peds trial. Issue 1 (8th September 2022) - Wadwa, R. Paul; Laffel, Lori M.; Franco, Denise R.; Dellva, Mary Anne; Knights, Alastair W.; Pollom, Robyn K.
Abstract: Aims: To evaluate the efficacy and safety of ultra‐rapid lispro (URLi) versus lispro in a paediatric population with type 1 diabetes (T1D) in a Phase 3, treat‐to‐target study. Materials and Methods: After a 4‐week lead‐in to optimize basal insulin, participants were randomized to double‐blind URLi ( n  = 280) or lispro ( n  = 298) injected 0 to 2 minutes prior to meals (mealtime), or open‐label URLi ( n  = 138) injected up to 20 minutes after start of meals (postmeal). Participants remained on pre‐study basal insulin (degludec, detemir or glargine). The primary endpoint was glycated haemoglobin (HbA1c) change from baseline after 26 weeks (noninferiority margin 4.4 mmol/mol [0.4%]). Results: Both mealtime and postmeal URLi demonstrated noninferiority to lispro for HbA1c: estimated treatment difference (ETD) for mealtime URLi −0.23 mmol/mol (95% confidence interval [CI] −1.84, 1.39) and postmeal URLi −0.17 mmol/mol (95% CI −2.15, 1.81). Mealtime URLi reduced 1‐hour postprandial glucose (PPG) daily mean ( P  = 0.001) and premeal to 1 hour postmeal PPG excursion daily mean ( P  < 0.001) versus lispro. The rate and incidence of severe, nocturnal or documented hypoglycaemia (<3.0 mmol/L [54 mg/dL]) were similar for all treatments. With mealtime URLi versus lispro, the rate of postdose hypoglycaemia (<3.0 mmol/L) was higher at ≤2 hours ( P  = 0.034). The incidence of treatment‐emergent adverse events was similar for all treatments. More participants reported an injection site reaction with mealtime URLi (7.9%) versus postmeal URLi (2.9%) and lispro (2.7%). Conclusions: In children and adolescents with T1D, URLi demonstrated good glycaemic control, and noninferiority to lispro in HbA1c change for mealtime and postmeal URLi. When dosed at the beginning of meals, URLi reduced 1‐hour PPG and PPG excursions versus lispro.